Investigation into the effect of phosphonate inhibitors on barium sulfate precipitation - Jones, Franca; Oliveira, Allan; Rohl, Andrew; Parkinson, Gordon; Ogden, Mark; Reyhani, Manijeh (Elsevier Science, 2002)
The effect of a series of phosphonate molecules on barium sulfate precipitation was tested. While an increase in the number of phosphonate groups generally resulted in increased inhibition of barium sulfate precipitation, two notable exceptions showed that a relatively high number of phosphonate groups does not guarantee inhibition while a relatively low number of phosphonate groups does not imply no inhibition. Increasing the pH showed an increased effect of additives on barium sulfate precipitation up to pH 8. However, on increasing from pH 8 to 12, a loss of inhibition in the additives was observed which appears to be due to the barium sulfate surface changing with pH.